The possibility of increasing production efficiency of al alloys applying electromagnetic field - Z. Gulišija; A. Patarić; M. Mihailović (Metalurgija, 2011)
The relationships between electromagnetic frequency, microstructure and mechanical properties of continuous casting aluminum alloys were studied in this paper. EN AW 2024 and EN AW 2007 aluminum alloys ingots were produced by electromagnetic continuous casting process. The microstructure and mechanical properties of as cast ingots were examined. The results showed that electromagnetic field, especially low frequency electromagnetic field, greatly influenced the microstructure and mechanical properties of as cast ingots. The significant energy savings and product quality can be achieved by the application of a proper frequency.